Elaborate ultrastructure of the Hirudo (Annelida: Hirudinae) cocoon surface. (11th December 2017) - Saidel, William M.; Saglam, Naim; Salas‐de la Cruz, David; Saunders, Ralph; Shain, Daniel H.
Abstract: Species of medicinal leeches ( Hirudo medicinalis, H. verbana, and H. sulukii) secrete hard‐shelled cocoons. When initially deposited, a cocoon is surrounded by a foam. Over a short time, the foam is transformed into a three‐dimensional structure. We show here that this peripheral structure likely forms by the solidification and dehydration of a moderately viscous, proteinaceous substance that surrounds bubbles of various sizes. The resulting matrix‐like structure comprises a network of curved branches juxtaposed at ∼120° and taper in width as a function of distance from the outer cocoon wall. The material is proteinaceous, and traps environmental material in its composition, especially silicon. The geometry of compartments and abundance of silicon on branch surfaces suggest a mechanism for trapping water to prevent desiccation in a terrestrial environment. Abstract : Hard‐shelled cocoons of medicinal leeches are surrounded by a three‐dimensional structure. This structure is likely formed by the solidification and retraction of a viscous, proteinacious substance that surrounds air bubbles of various sizes.